Pengaruh Jumlah Penambahan Graphene Nanosheets (GNSs) Dan Gliserol Terhadap Sifat Mekanis Coating Komposit Berbasis Polyvinyl Alcohol (PVA) - Abdul Rasyid Amrin; Amun Amri; Aman Aman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Polyvinyl alcohol (PVA) based conductive coatings composite wih the addition of graphene nanosheets (GNSs) have been successfully synthesized. Composites were synthesized using the solution mixing method and were tested their conductive properties, mechanical properties (tensile strength, elongation at break, and young modulus), morphology, and functional group analysis. The results showed that the addition of graphene increased the electrical conductivity, tensile strength, and Young modulus, but decreased elongation at break composite coating. Addition of glycerol increased elongation at break, but decreased the electrical conductivity, tensile strength, and Young modulus. The highest electrical conductivity was 1.11 x 10-3 s/m obtained by adding 3% graphene, the highest tensile strength was 25,894 MPa obtained by adding 3% graphene, the highest elongation was 250.862% obtained by adding 2%wt glycerol, and the highest modulus young was 18,496 MPa obtained by adding 3% graphene. Based on the results of the study, the PVA-based conductive composite coating with the addition of graphene nanosheets has a good perspective to develop further. Keywords: coating composite, glycerol, graphene, PVA